Influence of Emollient on the Preparation and stability of Sodiun Ascorbyl Phospate Cream - Yanni Dhiani Mardhiani; Deny Puriyani Azhari; Silviana Wulansari (Universitas Padjadjaran (Unpad), 2019)
As a type of cosmetic preparation products, cream dosage form is widely used with the addition of active substances having antioxidant activities, such as vitamin C and its derivatives. Sodium ascorbyl phosphate (SAP) can be used in topical formulation due to its more stable properties than ascorbic acid. However, it is difficult to deliver SAP into the dermis in a suficient dose. To overcome the problem, occasionally we can add a penetration enhancer. In some literature, emollients that often added in cosmetic preparations also have another effect as a penetration enhancer. The purpose of this research was to observe wether emollient addition could influence the penetration of SAP in the cream formulation or not. SAP was formulated into four formulations with three different emollients: dimethicone (F1), capric triglyceride (F2), and isopropyl myristate (F3) and a formulation without the addition of emollients (F4). The diffusion test was performed by Franz's diffusion cell method using male wistar rat’s abdominal membrane as a standard model of the skin barrier. The result of stability test showed that SAP cream was stable at room temperature but unstable on freeze thaw condition described by significant different values for all formulas. Nonetheless, the diffusion test showed that F2 with the capric triglyceride as emollient had the highest ability to pass SAP through the membrane, followed by isopropyl miristate. We concluded that emollient addition could influence the penetration of the cream of SAP.Keywords: vitamin c, ascorbic acid, sodium ascorbyl phospate, emollient, penetration enhancer